Technology orientation and export performance: The moderating role of supply chain agility - Zaina Nakabuye; Jamiah Mayanja; Sarah Bimbona; Micheal Wassermann (Modern Supply Chain Research and Applications, 2023)
Purpose - The purpose of this paper is to investigate the relationships between technology orientations and export performance of small and medium-sized enterprises (SMEs). Design/methodology/approach - A quantitative research design was adopted for this study. The paper formulates hypotheses from the literature review. These hypotheses are tested using structural equation modeling with data collected from 231 SMEs in Uganda. Data were analyzed using SPSS version 23 and AMOS. Findings - The findings of this study showed technology orientation has a positive and significant relationship with the performance of Ugandan SMEs and that supply chain agility moderates technology orientation and export performance. Research limitations/implications - The study discusses the findings, advances limitations and managerial implications. It also suggests future research avenues. It proposes some recommendations to help Ugandan SMEs to form flexible supply chains, use the latest technology and create strong relationship ties with their partners in the supply chain. Practical implications - The study suggests that managers of Ugandan SMEs should use the latest technology in production, marketing, logistics and supply chain management which will enable them to respond quickly to customer tastes and preferences leading to higher levels of export performance. Originality/value - This study contributes to the literature on strategic management showing the reliability of scales used and the confirmatory of the factor structure. This study shows that in strategic management technology, orientation is critical in increasing export performance. This study has extended the resource-based view (RBV) and dynamic capabilities theories.
Keywords: 650; Export performance; Supply chain agility; Technology orientation